CIS-MAKOBA: INOVASI SELF MONITORING CATATAN IBADAH SISWA BERBASIS WEB - Alim, Muhammad Rofiul; Puspitasari, Intan Nuyulis Naeni (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
The current transformation of conventional learning into digital (online) learning has substantially required adequacy on planning, implementing, and learning outcomes that utilize information and communication technology. Madrasah Aliyah Negeri Kota Batu has created the Web-based CIS-MAKOBA (Student Worship Notes-MAN Kota Batu) application to facilitate the distance learning process. It also can be part of responsive and innovative efforts in overcoming learning problems during the monitoring process that can relatively engender complaints from teachers, students, and parents. The main purpose of CIS-MAKOBA is a control and time management for students so that they can monitor the various activities that have been instilled in Madrasah. In so doing, they can actively participate non-academic fields at home. This CIS- MAKOBA was created through a research and development (R & D) process that has been designed based on the needs and conditions of the madrasah, validated by experts, and tested on a small or large scale, which shows feasibility with an average result of 87.9%.